CutFEM: Discretizing geometry and partial differential equations - Burman, Erik; Claus, Susanne; Hansbo, Peter; Larson, Mats G.; Massing, André (International journal for numerical methods in engineering, 2015)
Summary We discuss recent advances on robust unfitted finite element methods on cut meshes. These methods are designed to facilitate computations on complex geometries obtained, for example, from computer‐aided design or image data from applied sciences. Both the treatment of boundaries and interfaces and the discretization of PDEs on surfaces are discussed and illustrated numerically. Copyright © 2014 John Wiley & Sons, Ltd.